ADH2 regulation in the yeast Saccharomyces cerevisiae - Khoboko, Mojabatho Portia (University of the Free State, 2004)
The aim of this study was to investigate the ability of ethanol to repress the expression of ADH2 in the genome of Saccharomyces cerevisiae. To achieve this, an expression cassette (ADH2::LacZ) using LacZ as a reporter gene was constructed using the YIp356R shuttle vector. A 1000 bp up and downstream region, flanking the open reading frame of ADH2, was fused to the 5’-end and 3’-end of the LacZ gene in the YIp356R shuttle vector. Numerous attempts were made to transform the expression cassette (ADH2::LacZ) into S. cerevisiae (strain W303) containing a deleted ADH2 (adh2Δ::URA3), to displace the deletion cassette through homologous recombination, thereby placing ADH2::LacZ in the place of the ADH2 in genome of S. cerevisiae. This was unfortunately not successful and it was decided to use an alternative approach. In this case the expression cassette was cloned into the integrative vector YIplac211 and transformed into S. cerevisiae. For initial confirmation, the yeast transformants were grown on selective plates containing X-gal, which allows for the detection of β-galactosidase activity through the production of blue coloured colonies. The detection of the blue colour confirmed that the expression cassette was successfully constructed and integrated into the genome. Two randomly selected transformants were cultivated on 20 g glucose l-1 as sole carbon source, to study glucose repression and on three different ethanol concentrations to study the effect of ethanol on the expression of ADH2. Selection was maintained by growing the yeast in a URA– chemically defined media (pH 5.5) at 30ºC. Samples were taken at appropriate intervals to perform β-galactosidase assay, assess utilization of substrate (ethanol and glucose), ethanol formation and biomass determination. During growth on 20 g glucose l-1 the production of β-galactosidase was apparent only when glucose concentrations were very low (2.3 g l-1), indicating that glucose levels have to decrease to a critical level before ADH2 expression can resume. The highest final biomass was produced during growth on 20 g glucose l-1. During growth on the three different ethanol concentrations the highest β-galactosidase maximum specific activity was obtained during growth on 20 g ethanol l-1 (3 643 U mg-1) and the lowest during growth on 5 g ethanol l-1 (2 533 U mg-1). Although the maximum specific activity obtained during growth on 30 g ethanol l-1 were higher than that obtained during growth on 5 g l-1, the production rate was the lowest (93 U mg-1h-1) during growth on 30 g ethanol l-1, suggesting that 30 g ethanol l-1 concentration has negative effect on the expression of ADH2. However this slow production might have been due to the slow growth during this cultivation and not due to ethanol repression. The possible repression of ADH2 is further disputed by the high β-galactosidase production on 30 g ethanol l-1.

Hierdie studie was onderneem om vas te stel of etanol die uitdrukking van ADH2 onderdruk. Om dit te bepaal is ‘n uitdrukkings-kasset (ADH2::LacZ) waar LacZ gebruik is as verslaggewer-geen, gemaak deur gebruik te maak van die Yip356R pendelvektor. ‘n Eenduisend basispaar gebied, wat weerskante van die oopleesraam van ADH2 voorkom, is aan die onderskeie 5’- en 3’ kant van die LacZ geen geheg in die pendelvektor YIp356R. Verskeie pogings is aangewend om die uitdrukkings-kasset (ADH2::LacZ) in die gis Saccharomyces cerevisiae (stam W303) wat ‘n ADH2 delesie (adh2Δ::URA3) bevat, te transformeer om te lei tot die vervanging van die delesie-kasset deur middel van homoloë rekombinasie. Dit was egter nie suksesvol nie en ‘n alternatiewe prosedure is gevolg. In die geval is die uitdrukkings-kasset in die integrasievektor YIplac211 geplaas en getransformeer in die gis S. cerevisiae. Bevestiging vir die uitdrukking van β-galaktosidase is verkry deur die gemodifiseerde gisselle te groei op selektiewe plate wat X-gal bevat het en sodoende toelaat dat die teenwoordigheid van die ensiem β-galaktosidase bevestig kan word deurdat kolonies blou verkleur. Die verkleuring van kolonies het bevestig dat die uitdrukkings-kasset korrek voltooi is en in die genoom van die gis geïntegreer was. Twee transformante wat lukraak gekies is, is gegroei in medium wat 20 g glukose l-1 as enigste koolstofbron bevat het, om die effek van glukose repressie te bestudeer. Om die effek te bestudeer wat etanol uitoefen op die uitdrukking van ADH2, is drie verskillende konsentrasies etanol as enigste koolstof bron gebruik. Gisselle is gegroei in selektiewe URA- media (pH 5.5) by 300C. Monsters is geneem met aanvaarbare tussenposes om sodoende β-galaktosidase aktiwiteit, verbruik van koolstofbron (glukose en etanol), etanol vorming en biomassa te bepaal. Gedurende groei in die teenwoordigheid van 20 g glukose l-1 is die produksie van β-galaktosidase alleenlik waargeneem indien die vlak van glukose daal na ‘n konsentrasie van 2.3 g glukose l-1. Dit dui aan dat die vlak van glukose moet verlaag tot ‘n kritiese konsentrasie voordat ADH2 uitdrukking kan plaasvind. Die hoogste finale biomassa is geproduseer gedurende groei in die teenwoordigheid van 20 g glucose l-1. Gedurende groei op die drie verskillende konsentrasies etanol was die hoogste spesifieke aktiwiteit van β-galaktosidase waargeneem met groei op 20 g etanol l-1 (3 643 U mg-1) en die laagste vlak tydens groei op 5 g etanol l-1 (2 533 U mg-1). Alhoewel die hoogste spesifieke aktiwiteit van β- galaktosidase, wat waargeneem is gedurende groei op 30 g etanol l-1, hoër was as die aktiwiteit wat waargeneem is tydens groei op 5 g etanol l-1 was die produksie tempo van eersgenoemde (93 U mg-1h-1) die laagste. Dit mag moontlik aandui dat etanol teen ‘n konsentrasie van 30 gl-1 ‘n negatiewe effek het op die uitdrukking van ADH2. Dit is egter ook moontlik dat die laer produksie tempo die gevolg was van die verlaagde groei tempo en nie as gevolg van etanol onderdrukking nie. Die verhoogde β-galaktosidase produksie wys egter teen die moontlikheid van etanol onderdrukking op die uitdrukking van ADH2 in die teenwoordigheid van 30 g etanol l-1.
Dissertation (M.Sc.(Microbial, Biochemical and Food Biotechnology))--University of the Free State, 2004
Keywords: Saccharomyces cerevisiae; Alcohol dehydrogenase; Glucose repression; β-galactosidase; Ethanol inhibition